Integrated management of castor wilt disease: Integrated management of castor wilt disease - M SANTHA LAKSHMI PRASAD,; E BHARATHI,; B GAYATRI,; R D PRASAD, (Journal of Oilseeds Research, 2020)
Field trials were conducted for management of the wilt disease in castor during 2016-17 and 2017-18. Soilsolarisation during summer followed by seed treatment and soil application of carbendazim as well as soil solarisation along with seed treatment and soil application of Trichoderma harzianum were effective in reduction of wilt disease. Pathogen population had also decreased in soil samples collected at the time of harvest in plots with solarization, neem cake, and Trichoderma applied treatments.